Estrutura dos domínios meridionais da Zona de Ossa-Morena - Araújo, António (2022)
In this work, we present the main structural and metamorphic features of southern sector of Ossa-Morena Zone. The domain of Évora-Beja Massifs, near the suture zone, was deformed in lower structural level. This domain is affected by more deformation phases, the overall tectonics is earlier and the metamorphic peak reaches the blueschist facies. The Moura Philonitic Complex is interpreted as a tectonic “melange” at regional scale. The Estremoz-Barrancos Domain represents the upper structural level. The deformation is less intense and younger, the metamorphic grade is lower (low or very low-grade) and the sedimentary sequences are complete. The Santo Aleixo da Restauração thrust, the boundary between this two sectors, it corresponds to an earlier normal fault.